Food product optimization for quality and safety control : process, monitoring, and standards - Contreras-Esquivel, Juan Carlos; Badwaik, Laxmikant S.; Kannan, Porteen; Haghi, A. K. (Burlington, ON, Canada ; Boca Raton, Florida : Apple Academic Press, 2021)
"This book, Food Product Optimization for Quality and Safety Control: Process, Monitoring, and Standards, discusses food quality and safety standards that are critically important for both developed and developing economies, where consumer safety is among the primary issues to be considered in food supply chain management. After the rapid development of many economies, quality standards have focused on consumer demands for safe food and beverage. The book considers that food safety is a multi-faceted subject, using microbiology, chemistry, standards and regulations, and risk management to address issues involving bacterial pathogens, chemical contaminants, natural toxicants, additive safety, allergens, and more. This volume emphasizes the interrelationship between these areas and their equal importance in food production. With chapters from researchers from around the world, this book looks at critically important advances and topics in technology that has become indispensable in controlling hazards in the modern food industry. The varied topics include the role of mineral content of soils in food safety, microwave-assisted extraction of phenolic compounds, foodborne pathogenic anaerobes, enzymatic modification of ferulic acid content, and more. This volume is a valuable research-oriented reference for professionals and advanced students in food processing, as well as for those working in fields that service, regulate, or otherwise interface with the food industry"--
Transformation of phosphorus in soils of agroecosystems in long-term experiments : sustainability challenges of phosphorus and food / Rafail A. Afanas'ev, Genrietta E. Merzlaya, and Michail O. Smirnov.
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Quality; Food -- Analysis; Food -- Safety measures; Food additives; Food adulteration and inspection; SCIENCE / General; TECHNOLOGY / Food Science